2017
DOI: 10.1002/tox.22407
|View full text |Cite
|
Sign up to set email alerts
|

Cis -bifenthrin induces immunotoxicity in adolescent male C57BL/6 mice

Abstract: Bifenthrin (BF) is an important synthetic pyrethroid. Previous studies have demonstrated that cis-BF exhibits toxic effects on development, the neurological, reproductive and endocrine system. In this study, we evaluated the immunotoxicity caused by cis-BF in adolescent male C57BL/6 mice. Mice were exposed orally to 0, 5, 10, and 20 mg/kg/d for 3 weeks. The results showed that body weight, spleen weight, and splenic cellularity decreased in mice exposed to 20 mg/kg/d cis-BF. Additionally, we found that the mRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 39 publications
2
6
0
Order By: Relevance
“…The results of our study are similar to the results obtained by Wang et al who conducted an experiment on male mice exposed to bifenthrin for 3 weeks and confirmed immunotoxic effect of the pyrethroid [25]. Another study published by Wang et al elucidated the mechanisms of bifenthrin's immunotoxicity in murine macrophages.…”
Section: Discussionsupporting
confidence: 92%
“…The results of our study are similar to the results obtained by Wang et al who conducted an experiment on male mice exposed to bifenthrin for 3 weeks and confirmed immunotoxic effect of the pyrethroid [25]. Another study published by Wang et al elucidated the mechanisms of bifenthrin's immunotoxicity in murine macrophages.…”
Section: Discussionsupporting
confidence: 92%
“…A quintessential example is that ConA‐stimulated T cell proliferation in B6C3F1 female mouse splenocytes was inhibited by PFOS exposure . Our previous study demonstrated that the pesticide cis ‐bifenthrin inhibited the LPS‐ or ConA‐stimulated cell proliferation of primary cultured splenocytes . Consistent with these observations, the present study showed that 8:2 FTOH inhibited the splenocyte proliferation stimulated by ConA and LPS (Figure A,B), indicating that 8:2 FTOH inhibited both humoral and cellular immunity.…”
Section: Discussionsupporting
confidence: 89%
“…Dysfunction of the immune system can lead to autoimmune diseases, infections, and cancers . Until now, a number of studies have demonstrated that a wide range of xenobiotics can result in the disruption of immune function . FTOHs can be taken up via the breath and routine diet in mammals and then distributed through the bloodstream.…”
Section: Introductionmentioning
confidence: 99%
“…Intracellular ROS level is elevated by many xenobiotic substances, underlying the mechanism of caused cellular toxicity, including some PFASs . However, 6:2 FTOH and 8:2 FTOH did not cause oxidative DNA damage in rat testicular cells .…”
Section: Discussionmentioning
confidence: 94%
“…A broad range of industrial and environmental chemicals have been suggested to target immune system . It has been observed that the incidence of immune‐related diseases has been increasing throughout the recent decades, part of which can be traced back to an interference in immune function .…”
Section: Introductionmentioning
confidence: 99%